2012
DOI: 10.5688/ajpe767133
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Pharmacy Practice Experience in Application of Evidence-Based Policy

Abstract: Objective. To determine the impact of an advanced pharmacy practice experience (APPE) to develop skills needed to apply an evidence-based approach to population-level practice decisions. Design. A 4-week evidence-based medicine APPE was implemented that included active-learning techniques and online learning modules, participation in state drug-policy committee meetings, and completion of an evidence-based medicine review for a specific drug agent or class. Assessment. Students' mean score on application of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…This finding was similar to previously published studies [5][6][7][8]. Hester et al incorporated literature evaluation exercises in a primary care advanced pharmacy practice rotation and concluded that it had increased the students' understanding and strengthened their therapeutic recommendations [5].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This finding was similar to previously published studies [5][6][7][8]. Hester et al incorporated literature evaluation exercises in a primary care advanced pharmacy practice rotation and concluded that it had increased the students' understanding and strengthened their therapeutic recommendations [5].…”
Section: Resultssupporting
confidence: 81%
“…Hester et al incorporated literature evaluation exercises in a primary care advanced pharmacy practice rotation and concluded that it had increased the students' understanding and strengthened their therapeutic recommendations [5]. A 4-week evidence based medicine (EBM) APPE utilizing active learning techniques, on line modules and attendance of drug policy committee meetings and drug reviews increased the students' evidence based skills and practices [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33 ( [28][29][30][31][32][33][34][35][36] However, only one study examined the impact of a longitudinal EBM curriculum, and we previously reported our experience with integrating EBM into a didactic pharmacoeconomics course assignment. 37,38 Because little is known about the attitudes and perceptions of student pharmacists towards EBM, our objective was to describe our longitudinal EBM curriculum and to evaluate these aspects among student pharmacists after exposure to an EBM course that uses interactive pedagogical methods, along with a longitudinal EBM curriculum.…”
Section: A J P Ementioning
confidence: 99%